The Correlation of Body Mass Index with Sputum Conversion Time in MDR-TB Patients Undergoing Treatment with Short Term Regimen at H. Adam Malik Medan General Hospital - Diana Santy; Parluhutan Siagian; Bintang Yinke Magdalena Sinaga; Putri C Eyanoer (Jurnal Respirologi Indonesia, 2020)
Background: It was estimated about 10.4 million incidence of TB cases worldwide, of which 580,000 were MDR TB cases in 2015, however, only 125,000 were successfully found and treated. The World Health Organization (WHO) issued a recommendation of 9-11 month Short Term Regimen (STR) guideline that could provide satisfactory results in terms of successfull outcome, easier to control and also low-cost. The study aimed to analyze the correlation between Body Mass Index (BMI) and sputum conversion time in MDR TB patients undergoing treatment with STR and to determine the final treatment outcome using STR at H. Adam Malik Medan General Hospital, North Sumatra, Indonesia. Methods: This was a case series study of a total 76 MDR TB patients undergoing treatment using STR. Samples were obtained from medical record of the pulmonary isolation ward and MDR TB clinic at H. Adam Malik Medan General Hospital. Data were analyzed descriptively to identify the trend in sputum conversion from nine months of treatment. Results: The number of patients with normal BMI was 51.3% higher than those of low, very low and high BMI. The time to sputum conversion occured in the second month of treatment. All groups of BMI categories experienced conversions and normal BMI was higher in number. At the end of the treatment evaluation, the cure rate was 44.8%, the drop out was 28.9%, the regimen change was15.8%, died 9.2%, and moved 1.3%. Conclusion: There was a significant correlation between BMI and sputum conversion time in MDR TB patients. Good nutritional status was a predictor of treatment success.